Uncertainty about Length of the Monetary Policy Transmission Lag: Implications for Monetary Policy - Yuong Ha (Sveriges Riksbank, 1999)
Using stochastic simulations of the Reserve Bank of New Zealands macroeconomic model, this paper examines the implications for monetary policy of uncertainty about the length of the monetary policy transmission lag. Uncertainty is examined from two perspectives. The first investigates the robustness of efficient inflation-forecast-based rules under transmission lag uncertainty. Robustness, in this paper, is measured by the variability of the stabilisation properties of policy rules. The results indicate that rules that are less aggressive and more forward looking are more robust than rules that are more aggressive and less forward looking. By using more-robust rules, policy makers are more likely to achieve outcomes that are closer to what they expect. However, while less aggressive and more forward-looking rules are more robust, the implication for monetary policy is less clear. Typically, these more-robust policy rules have higher absolute levels of inflation variability than less-robust rules. In other words, less-robust rules typically do a better job at controlling inflation regardless of the transmission lag and regardless of what the central bank believes the transmission lag to be. The second aspect asks, if the central bank is uncertain about the length of the transmission lag, is it better to overestimate or underestimate the lag? If the central bank overestimates the lag, it believes inflation is harder to control than it really is. As a result, policy responses tend to be stronger than would be the case if the central bank knew the truth. Underestimating the lag has the opposite effect the central bank believes inflation is easier to control and policy responds less aggressively than would be the case if the central bank knew the truth. This result suggests that it is better to overestimate the transmission lag. By behaving as if inflation is harder to control, the central bank is able to counter inflationary pressures earlier and do a relatively better job at stabilising the economy.
Keywords: E50; 330; Monetary policy; Transmission uncertainty